Analysis Wastewater Treatmen and Environmental Policy Development: Bibliometrics and Visualization - Washilla Audia; Frinaldi, Aldri; Lanin, Dasman; Rembrandt, Rembrandt; Umar, Genius; Yulkifli, Yulkifli; Syah, Nurhasan; Nofriandi, Alwi; Aprilliani, Cici; Amelia, Kiki; Batubara, Fanny Yuliana; Hatika, Rindi Genesa; Febrina, Cory; Yasril, Abdi Iswahyudi; Hendrita, Juli (Postgraduate School, Universitas Negeri Padang, 2025)
The global water pollution crisis exacerbated by anthropogenic activities demands effective integration between science and policy. This study conducted a comprehensive bibliometric analysis of 285 publications to map the intellectual landscape and evolutionary trajectory at the interface of liquid waste contamination and environmental policy. Findings reveal an exponential acceleration of research since 2014, with 75.78% of publications concentrated in the last decade, reflecting increasing global urgency. China dominates as the research epicenter with the highest productivity (56 publications), the greatest citation impact (1,914 citations), and a role as a key collaboration link. Thematic analysis confirms the consolidation of this field around the core concepts of “environmental policy” (228 occurrences) and “wastewater treatment” (215 occurrences), marking a paradigm shift from technocratic approaches toward holistic policy integration. However, the polarization of international collaboration into 10 cohesive clusters indicates a fragmentation of global discourse. Critically, this study identifies an alarming disparity between rapid scientific progress and lagging policy adoption capacity, highlighting the urgent need for adaptive policy frameworks and transdisciplinary collaboration mechanisms to bridge the implementation gap and respond more effectively to emerging contaminants.